Deconstruction of the Romantic Myths in Slovenian Literature after France Prešeren - Cmiel-Bażant, Marta (Poznańskie Studia Slawistyczne, 2023)
The main aim of this article is to present the methods in which Slovenian myths of Romantic provenience, present in France Prešeren’s poetry, are deconstructed since the fifties of nineteenth century. Prešeren (1800−1849) is regarded as the national poet, who enabled the Slovenian community and competed with the canon of European literature. Parallelly to the process of his canonization occurred the reverse of it, The Anxiety of Influence, described by Harold Bloom. Poets Simon Jenko (1835−1869) and Oton Župančič (1878−1949) had been deconstructing the myths of Romantic love, mythical conception of poetry, poets and nation in the period of realism and modernism, as well as the poet Veno Taufer in the period of neo-avantgarde (1933−). The intertextual analysis of their poems shows several ways of contesting the influence of the main topics and aesthetic codes from Prešeren’s poetry, determined by the role of poetry in Slovenian culture, described in the late sixties of twentieth century as Prešeren structure.